2019 IEEE Information Theory Workshop (ITW) 2019
DOI: 10.1109/itw44776.2019.8989262
|View full text |Cite
|
Sign up to set email alerts
|

Improved Storage for Efficient Private Information Retrieval

Abstract: We consider the problem of private information retrieval from N storage-constrained databases. In this problem, a user wishes to retrieve a single message out of M messages (of size L) without revealing any information about the identity of the message to individual databases. Each database stores µM L symbols, i.e., a µ fraction of the entire library, where 1 N ≤ µ ≤ 1. Our goal is to characterize the optimal tradeoff curve for the storage cost (captured by µ) and the normalized download cost (D/L). We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 41 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…Though repetition coding can offer simplicity in designing PIR schemes and the high immunity against server failures, it suffers from extremely large storage cost. The storage cost in a PIR system has been widely investigated in terms of the coding structures in the storage design, such as specific Maximum Distance Separable (MDS) codes [3], [25], [37], an uncoded storage [26], [1], [31], and other more complicated coding techniques [20], [10], [5], [19], [36], [14], [2]. Moreover, the tradeoff between the storage cost and retrieval rate was considered without any explicit constraints on the storage codes [24], [29], [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though repetition coding can offer simplicity in designing PIR schemes and the high immunity against server failures, it suffers from extremely large storage cost. The storage cost in a PIR system has been widely investigated in terms of the coding structures in the storage design, such as specific Maximum Distance Separable (MDS) codes [3], [25], [37], an uncoded storage [26], [1], [31], and other more complicated coding techniques [20], [10], [5], [19], [36], [14], [2]. Moreover, the tradeoff between the storage cost and retrieval rate was considered without any explicit constraints on the storage codes [24], [29], [30].…”
Section: Introductionmentioning
confidence: 99%
“…by the independence of the files(2) and the fact that queries are independent of the files(8); (e) and (f ) follow by simply changing the summation indices; (g) follows fromK⊆[1:K]\{θ},|K|=k H(W θ |Z N ) = K−1 k H(W θ |Z N ); (h) follows from the definition of λ n in (59).Notice that when n ∈ [0 : N − 1] and k = K − 1, all the files W 1:K are presented in the conditions of each entropy function in T (n, k). Since the answers A[θ] [1:N ]\N is a function of Q [θ][1:N ]\N and W 1:K by (9), we have T (n, K − 1) = 0.…”
mentioning
confidence: 99%
“…Attia et al considered the case when the storage servers can only store uncoded segments of the messages [7], [8], and derived the full storage-retrieval tradeoff in such systems. A generalized code construction unifying the two codes was presented more recently in [9]. Mathematically, we use α to denote the normalized average storage per server per message bit, and β for the normalized average download cost per server by message bit (the precise definitions are given in Section II).…”
Section: Introductionmentioning
confidence: 99%
“…2) A cyclic permutation lemma that can produce more sophisticated codes from simpler ones: This is a general technique, and it can be shown that uncoded storage PIR code [7], [8] can be obtained directly from the code in [4] with this lemma, and the generalized MDS-PIR code [9] can be obtained from that in [6].…”
Section: Introductionmentioning
confidence: 99%
“…In two recent works [11,22], the tradeoff was considered without any structural constraints on the storage or retrieval codes for the special case of two databases and two messages, and it was found that non-linear codes can provide further improvement over linear codes. Other notable efforts can be found in [23][24][25][26][27] and references therein.…”
Section: Introductionmentioning
confidence: 99%